Rol de enfermería en el manejo del paciente crítico ventilado con sedoanalgesia - González Villegas, Gianni Darren (2024)
Sedoanalgesia, a crucial aspect of patient care, is applied to patients undergoing diagnostic or surgical interventions or when their health status is categorized as critical. This approach, which involves administering medications called sedatives and analgesics, is instrumental in reducing suffering and other discomforts. However, it can have adverse effects such as respiratory depression, hypotension, bradycardia, delirium, and withdrawal syndrome. In light of this, our work was carried out to systematize the nursing role in the comprehensive management of critically ill patients ventilated with sedation. We have described the characteristics of the patients and professionals involved and identified the key nursing activities. These professionals are not only responsible for continuous assessment, medication administration, and prevention of complications, but also for offering crucial emotional support to the patient and family, recognizing the importance of addressing the emotional needs of the patient in addition to their physical care.